(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study evaluates life skill education programs that are offered in secondary schools. The focus of this research is on the degree to which these programs assist students in terms of their personal development, social skills, and academic accomplishment. It is necessary for students to learn life skills such as effective communication, good decision-making, creative problem-solving, and emotional management in order for them to be able to confront the challenges of adulthood with self-assurance and competence. The purpose of this research is to investigate the structure, content, and impact of life skills classes that are currently being taught in a variety of secondary schools. Through the use of a variety of qualitative and quantitative research methods, such as questionnaires, interviews, and focus groups with students, instructors, and education authorities, the study was able to identify key strengths and areas for growth in these programs. According to the results, students’ academic achievement, interpersonal ties, and self-esteem are all positively influenced by life skills education that is carried out in an effective manner. Despite this, a great number of programs are unable to realise their full potential due to a variety of factors, such as inconsistent program implementation, poor teacher training, and limited financial resources. It is recommended in the study that adjustments be made to policies, chances for teachers to participate in professional development, and updates be made to current curriculum in order to increase the access that secondary school students have to education that focusses on life skills.